Edward Tryjarski, Armeno‑Kipchak Texts in the Alchemical Treatise by Andrzej Torosowicz (17th Century), Warsaw 2005, s. 266 - Zbigniew Szydło (Ksiegarnia Akademicka Publishing, 2010)
Edward Tryjarski, Armeno‑Kipchak Texts in the Alchemical Treatise by Andrzej Torosowicz (17th Century), Warsaw 2005, s. 266